2013
DOI: 10.1007/s11062-013-9374-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of L- and T-Type Calcium Channels in Regulation of Absence Seizures in Wag/Rij Rats

Abstract: In chronic experiments on five groups of WAG/Rij rats (a genetic model of absence epilepsy; six animals in each group), we recorded EEG activity from the S1po cortical area through implanted electrodes and subjected the cortex to the action of four agents affecting Land T-type calcium channels (injections through an implanted cannula). A blocker of L-type channels, verapamil hydrochloride, an agonist of these channels, Bay K8644, an antagonist of T-type calcium channels, L-ascorbate, and an agonist of the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Pharmacological modulation of the spike-wave activity using calcium channel blockers and activators has been shown in animals genetically predisposed to absence seizures. In particular, intraperitoneal and intracerebroventricular microinjections of L-type blockers resulted in an increase in the number and duration of SWDs, but intracortical microinjections suppressed SWDs [ 139 , 140 ].…”
Section: Cellular Targets Of Alpha2 Ars In Relation To Spike-wave Act...mentioning
confidence: 99%
“…Pharmacological modulation of the spike-wave activity using calcium channel blockers and activators has been shown in animals genetically predisposed to absence seizures. In particular, intraperitoneal and intracerebroventricular microinjections of L-type blockers resulted in an increase in the number and duration of SWDs, but intracortical microinjections suppressed SWDs [ 139 , 140 ].…”
Section: Cellular Targets Of Alpha2 Ars In Relation To Spike-wave Act...mentioning
confidence: 99%
“…Potassium channels led to the amplification of the hyperpolarization in neurons and activated T-type calcium channels and in fluxed calcium ions into the cell through these channels leading to burst activity of glutamatergic neurons. 11 Sadighi et al (2013) indicated that after PMA injectionan agonist of T-type calcium channels-into the somatosensory cortex, the number and duration of SWDs increased significantly in WAG/Rij rats. 21 In line with our study, an experiment on thalamus using voltage-clamp techniques implied that Ethosuximide reduces low-threshold calcium currents by cutting down the number of LTCC available channels, or creates a change in transduction across LTCC channels.…”
Section: Discussionmentioning
confidence: 99%
“…11 Sadighi et al (2013) indicated that after PMA injectionan agonist of T-type calcium channels-into the somatosensory cortex, the number and duration of SWDs increased significantly in WAG/Rij rats. 21 In line with our study, an experiment on thalamus using voltage-clamp techniques implied that Ethosuximide reduces low-threshold calcium currents by cutting down the number of LTCC available channels, or creates a change in transduction across LTCC channels. 22,23 Another study showed that microinfusion of 20 nmol of ETX into S1po in freely moving manner GAERS resulted in rapid and almost perfect suppression of SWDs in the whole cortex among both hemispheres compared to systemic administration of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…After these stages, the recorded data from before and after drug injection is analyzed and compared with each other. Since the injection of saline as control group had no significant effect on EEG and ECG recording in pervious papers of our college, 17 - 19 we used our prior data about the effect of saline injection. Therefore, we had no additional group for saline injection as control; the group before injection of CNT was considered as control group.…”
Section: Methodsmentioning
confidence: 99%